Correction: Inhibition of NLRP3 inflammasome activation and pyroptosis with the ethyl acetate fraction of Bungeanum ameliorated cognitive dysfunction in aged mice. Issue 18 (9th August 2021) - Zhao, Meihuan; Dai, Yuan; Li, Ping; Wang, Jie; Ma, Tengyun; Xu, Shijun
Abstract : Correction for 'Inhibition of NLRP3 inflammasome activation and pyroptosis with the ethyl acetate fraction of Bungeanum ameliorated cognitive dysfunction in aged mice' by Meihuan Zhao et al., Food Funct., 2021, DOI: ; 10.1039/D1FO00876E .